Freundschaft und Kirchenpolitik: Zwei Buchgeschenke Bullingers an Friedrich von Salis-Samedan - Bernhard, Jan-Andrea (Zwingliana, 2015)
The friendship between Heinrich Bullinger and Friedrich von Salis began incthe autumn of 1556. Unfortunately, several letters from this early period are missing. The recently discovered pair of book gifts from Bullinger to Salis can help to close this important gap. In addition, they also illustrate how Bullinger used his correspondence and book gifts for church political purposes.